The role of a small town in the flow of agricultural commodities with its hinterlands before and after the construction of the Trans Sumatra Toll Road (case study: Kalianda District South Lampung Regency Indonesia) - Ratu Nabillah; R. Rijanta; Rika Harini; Kamaru Abubakari (Universitas Negeri Malang, 2023)
Linkages between rural and urban areas assist numerous regions in a variety of ways. As a meeting place for villages and cities, a small town with hinterlands of agricultural areas acts as a market for village commodities, intermediary markets in larger markets, places for agricultural processing, places for production facilities, and a center for other activities. The construction of the Trans Sumatra Toll Road (JTTS), which crosses Kalianda District as a small town connecting several big cities, allows Kalianda alters its role. This study aims to examine the flow of agricultural commodities in a small town and its hinterlands and analyzed the role of small towns before and after the construction of JTTS. The data analysis was carried out by creating an Origin-Destination Map and providing the description. The results showed that seven agricultural commodities sold in Kalianda Market came from seven sources (origin), while commodities in rural areas had four selling destinations area. The small town illustrates its proper function as an intermediary market for larger markets, centers of health activities, administrative services, and banking services. However, the small town has not been able to play much of a role as an intermediary market for larger markets, rural commodity processing places, and places to find high-order goods. The small town is also incapable of being a destination for the identification of agricultural production facilities. In general, the existence of JTTS does not significantly change the role of small towns.